Applying Metallo‐Organic Ligand Design Principles to the Stereoselective Synthesis of a Peptide‐Based Pd2L4X4 Cage - Dr. Dominic F. Brightwell; Dr. Kushal Samanta; Dr. Jimmy Muldoon; Dr. Patricia C. Fleming; Dr. Yannick Ortin; Dr. Lina Mardiana; Dr. Paul G. Waddell; Dr. Michael J. Hall; Dr. Ewan R. Clark; Dr. Felipe Fantuzzi; Dr. Aniello Palma (ChemistryEurope)
Abstract The rational and controlled synthesis of metallo‐organic cages using polyaromatic ligands is well established in the literature. There is a strong interest to advance this field towards the use of chiral ligands capable of yielding cages in a stereoselective manner. Herein, we demonstrate that the classical approach for designing metallo‐organic cages can be translated to polyproline peptides, a biocompatible class of chiral ligands. We have successfully designed a series of polyprolines, which mimic the topology of ditopic polyaromatic ligands, to achieve the stereoselective synthesis of a novel Pd lantern cage. This cage exhibits excellent stability in water and demonstrates the stabilization of a highly reactive species in solution. This work will pave the way towards the stereospecific synthesis of more complex, functionalized peptide‐based metallo‐cages.